(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2010)
This cross-sectional study was conducted with the objective to assess the present status of activities related to quality assurance scheme (QAS) in medical and dental colleges of Bangladesh. The Principal or Vice principal or Academic coordinator was respondent and any one of them from each medical or dental college filled up a questionnaire. The study was conducted in 2008. Regarding the on going activities related to quality assurance scheme in their colleges, majority of the respondents mentioned that there are formal phase committees and course committee to run the quality assurance scheme, functioning faculty development and review scheme, continuing professional development activities like seminar etc., and mechanism to collect students’ feedback through structured questionnaire. Majority of them also mentioned that phase committees & course committee meetings held regularly, academic coordinator regularly met with the phase coordinators, student outcome analyzed, annual sports and cultural functions held regularly and recently they have submitted a report on the status of QA scheme to the Director Medical Education and Health Manpower Development (ME & HMPD). On the other hand most of them mentioned that the teachers of their respective medical colleges did not have adequate training on QAS, did not have adequate resources, designated staff for running QAS and functioning medical skill centre in the colleges and did not collect external examiners’ report. Most of the respondents recommended that teachers should be adequately trained on QAS, staff should be designated to run QAS and adequate resources should be allocated to run QAS and activities should be monitored and evaluated regularly. Key words: Quality assurance, medical education. DOI: 10.3329/jafmc.v5i2.4574 JAFMC Bangladesh Vol.5(2) (December) 2009, pp.5-7